Endoscopic ultrasound‐guided antegrade biliary stenting for unresectable malignant biliary obstruction in patients with surgically altered anatomy: Single‐center prospective pilot study. Issue 3 (8th February 2017) - Iwashita, Takuji; Yasuda, Ichiro; Mukai, Tsuyoshi; Iwata, Keisuke; Doi, Shinpei; Uemura, Shinya; Mabuchi, Masatoshi; Okuno, Mitsuru; Shimizu, Masahito
Abstract : Background and Aim: Endoscopic retrograde cholangiography (ERCP) with biliary stenting for the treatment of unresectable malignant biliary obstruction (MBO) is challenging among patients with surgically altered anatomy. Endoscopic ultrasound‐guided antegrade biliary stenting (EUS‐ABS) was introduced as an alternative biliary drainage method, although it has not yet been well studied. In this single‐center prospective pilot study, we aimed to evaluate the feasibility and safety of EUS‐ABS for MBO in patients with surgically altered anatomy. Methods: EUS‐ABS for MBO was attempted in patients with surgically altered anatomy. In EUS‐ABS, the bile duct in the left lobe was accessed from the intestine under EUS guidance, and a guidewire was placed. Thereafter, an uncovered metallic stent was deployed at the MBO through the fistula. All devices were then removed. Technical, clinical, and adverse event rates, as well as patient characteristics and procedure details, were evaluated. Results: Twenty patients (10 women; median age, 69 years) were enrolled in the present study. Technical and clinical success rates of EUS‐ABS were both 95% (19/20). In one patient, unsuccessful EUS‐ABS as a result of failed visualization of the left lobe of the liver with EUS was salvaged with percutaneous biliary drainage. Rate of adverse events was 20% (4/20), including mild pancreatitis in three patients and mild fever in one patient, which were successfully managed conservatively. Conclusions: EUS‐ABS for MBO in patients with surgically altered anatomy was a feasible and safe procedure. Further large scale comparison studies are needed to confirm its efficacy (Clinical Trial Registration Number: UMIN000008589).